High thermoelectric power factor of Poly(3-hexylthiophene) through in-plane alignment and doping with a molybdenum dithiolene complex - Untilova, Viktoriia; Hynynen, Jonna; Hofmann, Anna I.; Scheunemann, Dorothea; Zhang, Yadong; Barlow, Stephen; Kemerink, Martijn; Marder, Seth R.; Biniek, Laure; Müller, Christian; Brinkmann, Martin (Macromolecules, 2020)
We report a record thermoelectric power factor of up to 160 μW m-1 K-2 for the conjugated polymer poly(3-hexylthiophene) (P3HT). This result is achieved through the combination of high-temperature rubbing of thin films together with the use of a large molybdenum dithiolene p-dopant with a high electron affinity. Comparison of the UV-vis-NIR spectra of the chemically doped samples to electrochemically oxidized material reveals an oxidation level of 10%, i.e., one polaron for every 10 repeat units. The high power factor arises due to an increase in the charge-carrier mobility and hence electrical conductivity along the rubbing direction. We conclude that P3HT, with its facile synthesis and outstanding processability, should not be ruled out as a potential thermoelectric material.
Gesehen am 25.09.2020